2021
DOI: 10.1002/jcop.22785
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with county‐level mental health during the COVID‐19 pandemic

Abstract: The objective of this study is to determine county‐level factors associated with anxiety, depression, and isolation during the coronavirus disease 2019 (COVID‐19) pandemic. This study used daily data from 23,592,355 respondents of a nationwide Facebook‐based survey from April 2020 to July 2021, aggregated to the week‐county level to yield 212,581 observations. Mental distress prevalences were modeled using weighted linear mixed‐effects models with a county random effect. These models revealed that weekly perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Among these, age stands out, which had shown a direct relationship with depression in previous studies ( Cerecero-García et al, 2020 ; Hernández-Vásquez et al, 2020 ). At the onset of the COVID-19 pandemic, however, a higher prevalence of depression was observed in younger people, especially in the young adult group ( Alzahrani et al, 2022 ; Lupton-Smith et al, 2022 ; Shah et al, 2021 ; Wang et al, 2020 ; Xiong et al, 2020 ). In the present study, on the other hand, the association was not significant and the prevalence of CSDS was similar in all age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, age stands out, which had shown a direct relationship with depression in previous studies ( Cerecero-García et al, 2020 ; Hernández-Vásquez et al, 2020 ). At the onset of the COVID-19 pandemic, however, a higher prevalence of depression was observed in younger people, especially in the young adult group ( Alzahrani et al, 2022 ; Lupton-Smith et al, 2022 ; Shah et al, 2021 ; Wang et al, 2020 ; Xiong et al, 2020 ). In the present study, on the other hand, the association was not significant and the prevalence of CSDS was similar in all age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent feelings of depression and frequent feelings of anxiety were defined by a CTIS response of most of the time or all of the time , as used in other publications. 26 In March 2021, the wording was revised to ask participants how often they felt depressed or anxious over the last seven days instead of over the last five days , 27 motivating the dichotomization of the variables instead of using a continuous measure.…”
Section: Methodsmentioning
confidence: 99%
“…With its broad coverage of COVID-19-related inquiries, which includes mental health assessments, this survey stands as a key resource for the investigation of mental health trajectories across the world during the pandemic. In the context of the United States, researchers have analyzed both county-level and individuallevel data to assess the factors associated with anxiety, depression, and isolation during the pandemic (Lupton-Smith et al, 2022;Ettman et al, 2023;Kobayashi et al, 2023). Additionally, Kush et al (2022) observed a higher prevalence of anxiety symptoms among teachers compared to other professions.…”
Section: Introductionmentioning
confidence: 99%